A Refined Analysis of Superoxide Production by Mitochondrial sn-Glycerol 3-Phosphate Dehydrogenase - Orr, Adam L. (American Society for Biochemistry and Molecular Biology, 2012)
The oxidation of sn-glycerol 3-phosphate by mitochondrial sn-glycerol 3-phosphate dehydrogenase (mGPDH) is a major pathway for transfer of cytosolic reducing equivalents to the mitochondrial electron transport chain. It is known to generate H(2)O(2) at a range of rates and from multiple sites within the chain. The rates and sites depend upon tissue source, concentrations of glycerol 3-phosphate and calcium, and the presence of different electron transport chain inhibitors. We report a detailed examination of H(2)O(2) production during glycerol 3-phosphate oxidation by skeletal muscle, brown fat, brain, and heart mitochondria with an emphasis on conditions under which mGPDH itself is the source of superoxide and H(2)O(2). Importantly, we demonstrate that a substantial portion of H(2)O(2) production commonly attributed to mGPDH originates instead from electron flow through the ubiquinone pool into complex II. When complex II is inhibited and mGPDH is the sole superoxide producer, the rate of superoxide production depends on the concentrations of glycerol 3-phosphate and calcium and correlates positively with the predicted reduction state of the ubiquinone pool. mGPDH-specific superoxide production plateaus at a rate comparable with the other major sites of superoxide production in mitochondria, the superoxide-producing center shows no sign of being overreducible, and the maximum superoxide production rate correlates with mGPDH activity in four different tissues. mGPDH produces superoxide approximately equally toward each side of the mitochondrial inner membrane, suggesting that the Q-binding pocket of mGPDH is the major site of superoxide generation. These results clarify the maximum rate and mechanism of superoxide production by mGPDH.